2022
DOI: 10.1259/bjr.20220374
|View full text |Cite
|
Sign up to set email alerts
|

Role of intratumoral and peritumoral CT radiomics for the prediction of EGFR gene mutation in primary lung cancer

Abstract: Objectives To determine the added value of combining intratumoral and peritumoral CT radiomics for the prediction of epidermal growth factor receptor (EGFR) gene mutations in primary lung cancer (PLC). Methods This study included 478 patients with PLC (348 adenocarcinomas and 130 other histological types) who underwent surgical resection and EGFR gene testing. Two radiologists performed segmentation of tumors and peritumoral regions using precontrast high-resolution CT images, and 398 radiomic features (212 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…In our study, the accuracy of FDG PET texture indices ranged from 0.621 to 0.712. Yamazaki et al evaluated 14 intratumoral and 18 peritumoral CT radiomics for the prediction of EGFR mutation in lung cancer 18 . The AUCs of intratumoral CT radiomics and combined intratumoral and peritumoral CT radiomics were 0.730 and 0.774, respectively 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the accuracy of FDG PET texture indices ranged from 0.621 to 0.712. Yamazaki et al evaluated 14 intratumoral and 18 peritumoral CT radiomics for the prediction of EGFR mutation in lung cancer 18 . The AUCs of intratumoral CT radiomics and combined intratumoral and peritumoral CT radiomics were 0.730 and 0.774, respectively 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki et al evaluated 14 intratumoral and 18 peritumoral CT radiomics for the prediction of EGFR mutation in lung cancer 18 . The AUCs of intratumoral CT radiomics and combined intratumoral and peritumoral CT radiomics were 0.730 and 0.774, respectively 18 . In our study, the AUCs of FDG PET texture indices ranged from 0.662 to 0.753.…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki et al reported the usefulness of 3 mm-peritumoral radiomic features for predicting EGFR mutation status. 10 Furthermore, Morales et al reported that peritumoral lung parenchyma within 3 mm excluding the thoracic wall or mediastinum was correlated with overall survival in lung cancer. 29 Therefore, the use of IPRS3 is reasonable and meaningful for predicting the EGFR mutation status.…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki et al and Choe et al reported the usefulness of peritumoral radiomic features in predicting EGFR mutation status. 1,10 Their methods used a single setting with peritumoral sizes of 3 and 5 mm from the tumor border. Because the studies used different peritumoral size, optimal peritumoral size for predicting EGFR mutation status must be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation